Bartsia lydiae, a new species of Bartsia sect. Laxae (Orobanchaceae) from the southern Peruvian Andes with a revised key to Bartsia sect. Laxae - Sylvester, Steven Paul (Phytotaxa, 2014)
A new species of Bartsia sect. Laxae is described and illustrated from the Cordillera Vilcanota, southern Peru. The species is distinct from all other members of sect. Laxae in being covered with persistent glandular hairs and having a reddish purple corolla. The species is a common element of undisturbed puna vegetation in the Cordillera Vilcanota, being associated with Polylepis forests. A revised key to Bartsia sect. Laxae is included to accommodate this new species.